2005
DOI: 10.1107/s0108270105004701
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethyl derivatives of pentacyclo[5.4.0.02,6.03,10.05,9]undecane

Abstract: Three cage-like polycyclic compounds, viz. exo-8-(trifluoromethyl)pentacyclo[5.4.0.0(2,6).0(3,10).0(5,9)]undecan-endo-8-ol, C12H13F3O, 5-(trifluoromethyl)-4-oxahexacyclo[5.4.1.0(2,6).0(3,10).0(5,9).0(8,11)]dodecan-3-ol, C12H11F3O2, and N-[exo-11-(trifluoromethyl)-endo-11-(trimethylsilyloxy)pentacyclo[5.4.0.0(2,6).0(3,10).0(5,9)]undecan-8-ylidene]aniline methanol solvate, C21H24F3NOSi.CH4O, were obtained from the corresponding oxo derivatives by nucleophilic trifluoromethylation with (trifluoromethyl)trimethyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…ORTEP-plots for compounds 13 and 21. 13 Noteworthy, the transannular cyclization under trifluoromethylation conditions was previously reported for the reaction of a 1,5-dione (i.e. bicyclo[3.3.1]nonane-2,6-dione) but in this case the successful formation of the product of bis-trifluoromethylation was reported.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…ORTEP-plots for compounds 13 and 21. 13 Noteworthy, the transannular cyclization under trifluoromethylation conditions was previously reported for the reaction of a 1,5-dione (i.e. bicyclo[3.3.1]nonane-2,6-dione) but in this case the successful formation of the product of bis-trifluoromethylation was reported.…”
Section: Methodsmentioning
confidence: 99%
“…The transannular process has not been observed and even with an excess of 3 the C=N-group did not react. The X-ray analysis 13 showed that the CF 3 -group is placed at exo-position (Fig.1). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For examples of PCU cage structures that exhibit C-C bond lengths that deviate from the normal value, see: Flippen-Anderson et al (1991); Linden et al (2005). For similar structures, see: Kruger et al (2005Kruger et al ( , 2006; Karpoormath et al (2010).…”
Section: Related Literaturementioning
confidence: 99%